New Perspectives on Microsoft Project 2000 - Rachel, Biheller-Bunin (Cengage Learning, Inc, 2000)
Part of our New Perspectives Series, this text offers a case-oriented, problem-solving approach to teaching students about Microsoft Project 2000. It's a perfect add-on for any Project Management course